Monitoring muscle oxygen asymmetry as a strategy to prevent injuries in footballers - Vasquez Bonilla, A. A.; Brazo-Sayavera, J.; Timón, R.; Olcina, G. (Research Quarterly for Exercise and Sport, 2023)
Purpose It has been hypothesized that sports injury risk is explained by muscle metabolism. The objective was to evaluate the muscle oxygen saturation slopes (?SmO2 slopes) and muscle oxygenation asymmetry (MO2Asy) at rest and to study their associations with injuries during the pre-season.